Effectiveness comparison of atorvastatin vs. rosuvastatin in reducing CRP level in acute coronary syndrome: A systematic review and meta-analysis - I Gusti Ayu Inten Heny Pratiwi; Anak Agung Gde Waisampayana Putra (Intisari Sains Medis, 2022)
Background: Acute coronary syndrome (ACS) is a group of various clinical symptoms, including acute myocardial ischemia. When administered for coronary artery instability, one of the targets for statins is to reduce inflammation factor-like c-reactive protein (CRP). Increased levels of CRP are related to ischemic heart disease. Therefore, a meta-analysis was assessed to compare atorvastatin vs. rosuvastatin as the most effective for reducing CRP of a patient with acute coronary syndromeMethods: We searched PubMed and Cochrane databases until October 23th 2020. Search terms included acute coronary syndrome, C-reactive protein or CRP, rosuvastatin, atorvastatin, randomized, random, and randomization. We excluded study populations with acute kidney injury/dyslipidemia/metabolic syndrome. All analyses in our study were carried out using Review Manager version 5.3 (RevMan Cochrane, London, UK).Result: We have found four eligible studies (487 patients) were included. Funnel plots and p-Egger were inspected to assess publication bias. The pooled analysis demonstrated the benefit of atorvastatin or rosuvastatin over therapy for all studies. The result shown (WMD: 2.41; P=0.06; 95% CI: -0.07 – 4.90) on the forest plot.Conclusion: Our meta-analysis clarifies that atorvastatin, compared to rosuvastatin, or vice versa, is not statistically significant in reducing CRP in acute coronary syndrome patients.